Effects of calcium and/or boron deficiency on the peduncle of sunflower inflorescence - Baumgartner, José Geraldo; Andreatta, José Antonio; Júnior, Alphio Formigoni (Pesquisa Agropecuaria Brasileira, 2014)
Sunflower (Helianthus annuus L.) cv. Anhandy was grown in a greenhouse for 60 days in a modified Steimberg nutrient solution. A 5 x 5 factorial combination with five levels of calcium and five levels of boron was used. The purpose of the experiment was to induce slow symptons, at flowering time, of calcium and boron deficiency. Calcium deficiency gave rise to a colapse of the flower-head, only when initial calcium level of the nutrient solution (15.24 ppm Ca) allowed the appearance of the symptoms, at the beginning of the flowering time. The boron deficiency symptoms appeared before the flowering time for all the initial levels of this micronutrient in the solution, and in this case its evaluation in relation to the flower-head was not possible to be done.